(untitled) (Bangladesh Journal of Child Health, 2024)
Hand-foot-and-mouth disease (HFMD) is a common self-limiting viral infection in children caused by Coxsackievirus A16 and human enterovirus 71, presenting with fever, erythematous papulovesicular eruptions/ blisters on the palms, soles, knees, buttocks, and oral mucosa. Although rare, complications may arise in nails e. g. onychomadesis (nail separation) and Beau’s lines (transverse lines on the nails). These typically appear within four to eight weeks of HFMD and persist for around 5-6 weeks. No active treatment is required and these nail changes resolve spontaneously within few weeks as the nail bed remain intact. We present here a boy of 4 years who presented with such nail changes after around 5 weeks of HFM disease and diagnosed as onychomadesis and Beau’s lines after ruling out other possible causes of nail changes. BANGLADESH J CHILD HEALTH 2023; VOL 47 (1) : 47-50